The Impact of the Tsaqifa Method on Elderly Qur'an Reading Skills - Ardianto, Risko Aris; Rohimah, Siti (Universitas Islam Negeri Sumatera Utara, 2025)
This study aims to analyze the effect of the Tsaqifa method on the Qur'anic reading ability of elderly learners at TPQ Masjid Arofah. The Tsaqifa method is a learning approach designed to enhance fluency and comprehension in reading the Qur'an, particularly among elderly students who may face challenges in learning due to age-related factors. This research employs a quantitative approach using an experimental method. A purposive sampling technique was used to select 16 elderly students as respondents. Data were collected through Qur'anic reading tests and analyzed using validity, reliability, and normality tests, as well as Pearson Product Moment correlation with the aid of SPSS 25.0 software. The results indicate that the research instrument is valid and reliable, with a Cronbach’s Alpha value of 0.863. The data distribution is normal, with a significance value of 0.067 (>0.05). The assessment of the Tsaqifa method shows that 56.25% of students fall into the high category, 31.25% in the moderate category, and 12.5% in the low category. The Qur'anic reading ability of students is also categorized as moderate to high, with a correlation value of r = 0.690, which is higher than the r table value. This confirms a positive and significant effect of the Tsaqifa method on improving the Qur'anic reading skills of elderly learners. The implications of this study suggest that the Tsaqifa method can be used as an effective strategy in Qur'anic learning at TPQ. The findings are expected to serve as a reference for educators in selecting more innovative and effective teaching methods for elderly learners.